Decentralized Justice: A Comparative Analysis of Blockchain Online Dispute Resolution Projects - Aouidef, Yann; Ast, Federico; Deffains, Bruno (Frontiers in Blockchain, 2021)
In recent years, the digital economy has experienced a growing number of transactions. Traditional dispute resolution methods such as court and international arbitration are ineffective for handling a large volume of small value claims across national borders. Decentralized justice is a new approach to online dispute resolution that combines blockchain, crowdsourcing and game theory in order to produce resolution systems which are radically more efficient than existing methods. This article offers a review of the decentralized justice industry and of the key players participating in it. It presents a number of key dimensions of the industry and reviews the mechanism design choices made by these different platforms. Finally, it discusses a growth hypothesis for the industry and how it may grow in the future.